Strategie per la conoscenza e il restauro del Paesaggio Culturale. Il caso dell’antico vigneto e del Palazzo Mansi ex Palazzo Vescovile di Scala (Sa) - Proto, Giulia (Restauro Archeologico, 2023)
The Palazzo Mansi and the ancient vineyard on terraces that surround it can be considered a large insula within the historic center of Scala, one of the 15 municipalities of the Amalfi coast, declared a World Heritage Site in 1997. The Mansi property, constituted by the ancient episcopal palace and vineyard on terraced land with some interesting minor buildings represents a whole to be analyzed and preserved as a system of built heritage and landscape. The main building consists of four floors: the two lowest floors have agricultural functions, as cisterns and cellars; the top ones, noble floors and the attic have maintained the original vaults, wooden floors and roofs, with limited adaptation interventions. The proposed essay aims to analyze the identity characteristics of this built landscape, which shows the values recognized by UNESCO in the Amalfi Coast area and which need new strategies for conservation and restoration to be handed down to posterity.